Targeted Therapies for Triple-Negative Breast Cancer: Combating a Stubborn Disease. (December 2015) - Kalimutho, Murugan; Parsons, Kate; Mittal, Deepak; López, J. Alejandro; Srihari, Sriganesh; Khanna, Kum Kum
Abstract : Triple-negative breast cancers (TNBCs) constitute a heterogeneous subtype of breast cancers that have a poor clinical outcome. Although no approved targeted therapy is available for TNBCs, molecular-profiling efforts have revealed promising molecular targets, with several candidate compounds having now entered clinical trials for TNBC patients. However, initial results remain modest, thereby highlighting challenges potentially involving intra- and intertumoral heterogeneity and acquisition of therapy resistance. We present a comprehensive review on emerging targeted therapies for treating TNBCs, including the promising approach of immunotherapy and the prognostic value of tumor-infiltrating lymphocytes. We discuss the impact of pathway rewiring in the acquisition of drug resistance, and the prospect of employing combination therapy strategies to overcome challenges towards identifying clinically-viable targeted treatment options for TNBC. Trends: Triple-negative breast cancers (TNBCs) account for ∼15–20% of all diagnosed breast cancer cases. TNBCs are themselves heterogeneous, composed of at least 4–6 definable molecular subtypes. Proliferative and survival-dependent pathways represent targets in TNBC. Other promising therapeutic targets in TNBC include those that control the cell cycle and the DNA damage responses. Acquisition of resistance to targeted therapies is a hurdle to overcome for effective TNBC therapy.